Management of giant cell arteritis among general practitioners from Genoa, Italy: a web-based survey - P. Clini; A. Stimamiglio; D. Camellino; E. Hysa; M. Cutolo; M.A. Cimmino (PAGEPress Publications, 2021)
Giant cell arteritis (GCA) is the most common form of vasculitis of the adult. General practitioners (GPs) are usually the first physicians who take care of GCA patients. In this study, the awareness of GPs from Genoa, Italy, regarding GCA was investigated by a web-based survey. A web-based questionnaire was sent by mail to 775 Italian GPs. It included 12 multiple choice questions regarding practice seniority, practice population size, number of GCA patients followed, and GPs' diagnostic and therapeutic approach. Of the 775 GPs involved, 76 (9.8%) answered. Thirty-three/75 (44%) declared that they did not see patients with GCA and the remaining 42 (56%) that they diagnose between one and two patients per year. New headache onset was the presenting feature of GCA for the majority of GPs (78.3%). GCA was diagnosed on the basis of clinical presentation alone by 35.2% of them, of temporal artery biopsy by 49.3%, and by imaging, including ultrasound and magnetic resonance imaging, by 15.5%. The referral pattern was mainly toward rheumatologists (68.5%). Only 27.8% GPs declared they start treatment at the first clinical suspicion, with the others waiting for laboratory and imaging examinations or specialist consultation. The doses of glucocorticoids used were in keeping with current guidelines. The management of GCA by GPs from Genoa is in general correct, with the exceptions of excessive confidence in headaches for diagnosis and of the timing of GC initiation. These points suggest that a program of information and education for GPs is warranted.